Do-it-yourself piano : [the best step-by-step guide to start playing] - Watson, Alistair (Musician); Watson, Alistair (Musician); Watson, Alistair (Musician) (Hal Leonard, 2022)
"Do-It-Yourself Piano is a fun way to get started playing on your own. Using over 90 well-known pop tunes and classical repertoire, you will be given step-by-step instructions on what you need to know to get started and sounding like a pro in no time. Includes over 170 audio tracks for demonstration and play-along, plus video instruction by piano teacher Alistair Watson."--provided by publisher.